Costing structure improvement using activity based costing in palm oil plantation of Malaysia - S. N. A. M., Zaini; C. W., Zheng; Mohd Yazid, Abu (Penerbit UMP, 2020)
Malaysia is one of the largest producers and exporters of palm oil in the world, accounting for 11% of the world's oils & fats production and 27% of the export trade of oils & fats. Oil palm tree will start bearing fruits after 30 months of field planting and will continue to be productive for the next 20 to 30 years. Thus, a proper costing method is very important in order to have a clear picture of its profit loss and gain for the next 20 to 30 years. The aim of this work is to apply the activity based costing (ABC) as a method of cost estimation for the palm oil plantation. The ABC has been applied to analyze the costing for every activity involved in the palm oil plantation. The actual cost information of each activity has been obtained through a process flowchart. Other than that, proper cost driver has been assigned in order to obtain the actual manufacturing cost of an oil palm plantation. The expected monthly manufacturing costs of xxx company has been calculated which is MYR 494303.04 and consequently the accurate profitability can be achieved. Accurate profitability is the most important factor for the management to identify the money that process in order to maintain rapid but sustainable growth. Therefore, ABC has assigned actual cost information and proper cost drivers for each of the activities being involved and it makes the company’s profitability more accurate.